2020
DOI: 10.1111/ppa.13318
|View full text |Cite
|
Sign up to set email alerts
|

Surfactants in plant disease management: A brief review and case studies

Abstract: In plant disease management, surfactants are generally used in combination with pesticides to facilitate delivery of the pesticide chemicals to the target sites in plants, vectors, or pathogens. Their intended use is rarely for direct effect on plant pathogens. However, trends in recent studies have revealed an appreciable increase in their use for direct management of plant diseases. In this paper, we briefly review the progress made in the use of surfactants for disease management, as adjuvants and when appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 119 publications
(185 reference statements)
0
22
2
Order By: Relevance
“…Currently, a range of chemically synthesized surfactants, such as Triton X-100, Cohere, Agral 90, Silwet L-77, and Tween 20, are some of the most common synthetic surfactants used for plant disease management, and they have displayed improved insecticidal potential during in vitro and in vivo applications [ 138 , 139 ]. However, due to its chemical and toxic nature, direct application on the plant surface was avoided.…”
Section: Biosurfactant Application In Plant Disease Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, a range of chemically synthesized surfactants, such as Triton X-100, Cohere, Agral 90, Silwet L-77, and Tween 20, are some of the most common synthetic surfactants used for plant disease management, and they have displayed improved insecticidal potential during in vitro and in vivo applications [ 138 , 139 ]. However, due to its chemical and toxic nature, direct application on the plant surface was avoided.…”
Section: Biosurfactant Application In Plant Disease Managementmentioning
confidence: 99%
“…Pseudomonas and Bacillus are the most common bacterial genera used for biosurfactant production. There are numerous reports available that showed their potency in biosurfactant production and their implication in successful phytopathogen management [ 138 ]. Varnier et al [ 144 ] reported on Rhamnolipid, produced by the Pseudomonas aeruginosa , which enhanced the immune response of grapevine against the Botrytis cinerea after application.…”
Section: Biosurfactant Application In Plant Disease Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a range of chemically synthesized surfactants such as Triton X-100, Cohere, Agral 90, Silwet L-77, Tween 20 are the some most common synthetic surfactant, has been available in the market used for plant disease management and displayed improve insecticidal potential during in vitro and in vivo applications [138,139]. However, due to its chemical and toxic nature, it avoided direct application on the plant surface.…”
Section: Biosurfactant Application In Plant Disease Managementmentioning
confidence: 99%
“…The surfactants have been shown to play a promising role in formulating agronanochemical products as they can reduce surface tension, maintain the turgidity of droplets on the target site and lower the pH solution to ensuring the ingredients to be preserved. The effect of different surfactants towards fungal disease in plants such as Fusarium head blight, Beauveria bassiana [ 8 ] and powdery mildew [ 9 ] have been reported recently. Currently, the study on the use of surfactants for the treatment of the Ganoderma boninense pathogen, a causal pathogen for BSR disease, is still lacking.…”
Section: Introductionmentioning
confidence: 99%